Deteksi Perubahan Garis Pantai Dengan Penggunaan Citra Satelit Landsat: Studi Kasus Kecamatan Seririt, Kabupaten Buleleng, Bali - Bhujangga, I Gede Sakti; Sila Dharma, I Gusti Bagus; Darmendra, I Putu Yogi (Journal of Marine Research and Technology, 2025)
Seririt District is a sub-district located in Buleleng Regency which has an area of 11,178 Ha with a coastline length of 11.61 Km and consists of 21 villages. Previous research found that in this sub-district there are several parts of the coast that will experience changes in the coastline due to coastal erosion or abrasion and sea level rise. This research was conducted in the Seririt District area through satellite images for the last 8 years using the Digital Shoreline Analysis System (DSAS) method which aims to determine changes in coastlines and area changes in the study area. The data used in this study are landsat 8 imagery data in 2015, 2017 and landsat 9 image data in 2022. This study obtained the results that changes in the coastline along Seririt District from 2015 to 2020 showed abrasion and accretion that occurred in each village with the highest abrasion and accretion impact occurring in Banjarasem Village with an abrasion impact of 52.34 m and an accretion impact of 26.84 m and the area that experienced changes in the coastline of Seririt District was 10.59 Ha due to abrasion and 1.84 Ha due to accretion .